Adaptive Leadership In The Era Of Disruption: Integrating Digital Transformation, Organizational Culture, And Teacher Performance (A Case Study Of Muhammadiyah High Schools In Cianjur Regency) - Abdul Haris; Nuraeni Nuraeni (Dinasti International Journal of Education Management And Social Science, 2025)
This study examines the role of adaptive leadership in addressing the challenges of the digital disruption era in two Muhammadiyah high schools in Cianjur Regency. The background of the research indicates that rapid changes in technology and organizational culture impact teachers' performance. The purpose of the study is to analyze the effects of digital transformation and organizational culture on adaptive leadership and its impact on teachers' performance. The method used is a quantitative approach with data analysis obtained from surveys and questionnaires. The results show that although adaptive leadership does not serve as a significant intervening variable, the influence of digital transformation and organizational culture still affects teachers' performance. The conclusion of this study emphasizes that to face the challenges of disruption, school leaders need to integrate supportive technology and organizational culture to create an innovative and responsive learning environment that meets current educational needs. This research provides practical insights for educational institutions in developing effective and sustainable leadership strategies.